Enhancing the Market Appeal of 'Pak Boss' Rice Bran Cereal Through Visual Packaging Design - Yasdaniar, Marsha Mafisa; Dwitasari, Putri; Alamin, Rabendra Yudistira; Sayatman, Sayatman (Universitas Ciputra, 2025)
Indonesia, as the second-largest rice producer in Asia and third globally, generates a significant amount of rice bran as a by product of the rice milling process. Despite its high nutritional value and potential for human consumption, rice bran remains underutilized.